Exploring variability in lithic armature discard in the archaeological record. Issue 155 (June 2021) - Gravel-Miguel, Claudine; Murray, John K.; Schoville, Benjamin J.; Wren, Colin D.; Marean, Curtis W.
Abstract: The invention of projectile technology had important ramifications for hominin evolution. However, the number of stone points that could have been used as projectiles fluctuates in archaeological assemblages, making it difficult to define when projectile technology was first widely adopted and how its usage changed over time. Here we use an agent-based model to simulate a hunter-gatherer foraging system where armatures are dropped according to their usage. We explore the impact of interactions between human behaviors and the environmental constraints of a data-informed landscape on the distribution and number of lithic armatures found in archaeological assemblages. We ran 2400 simulations modeling different population sizes, rates of hunting with projectiles, and tool curation levels. For each simulation, we recorded the location of dropped armatures and calculated the number and percentage of used armatures that were discarded at habitation camps vs. lost during hunting. We used linear regression to identify the demographic, behavioral, and environmental factor(s) that best explained changes in these numbers and percentages. The model results show that in a well-controlled environment, most armatures used as projectile weapons are lost or discarded at hunting sites; only ∼4.5% of used armatures (or ∼2 armatures per year of simulation) are discarded in habitation camps where they would likely be excavated. These findings suggest that even rare hafted armatures found in the Early and Middle Stone Age could indicate a well-established use of such tools. Our model shows that interactions between reoccupation of archaeological sites, population size, rate of hunting with projectile weapons, and tool curation levels strongly influence the count of lithic armatures found in archaeological assemblages. Therefore, we argue that fluctuations in the counts of armatures documented at archaeological sites should be evaluated within their demographic and environmental contexts to better understand if they reflect spatiotemporal changes in hunting behavior.